Cardiovascular risks in patients with psoriasis : A systematic review (Research, Society and Development, 2024)
Psoriasis is a chronic inflammatory disease characterized by immune mediated skin inflammation and hyperproliferation of keratinocytes, resulting in  erythematous plaques or papules covered with silvery scales, primarily affecting  extensor surfaces, nails, scalp, and trunk, often accompanied by itching and irritation  during active phases. It exhibits clinical variability and can manifest in various forms,  including plaque, nail, guttate, inverse, pustular, erythrodermic, and psoriatic. This  condition has a genetic predisposition, and when combined with environmental and  behavioral factors, plays a significant role in disease progression. The prevalence of  cardiovascular risk factors and metabolic disorders has been found to be high in  psoriasis patients, possibly due to the inflammatory nature common to both conditions.  Current studies suggest that the inflammatory nature of psoriasis may be linked to a  predisposition to other diseases with altered inflammatory status, particularly cardiovascular diseases. This study aims to provide a synthesis of current and relevant  information regarding the association between psoriasis and cardiovascular risk  factors. Information was obtained through a systematic review, of a descriptive and  exploratory nature, using the PRISMA method, searching for articles in the PubMed  and BVS databases with the keywords "Psoriasis," "Cardiovascular disease," and  "Risk factors." The review included articles from Controlled Clinical Trials published  between 2018 and 2023, demonstrating the connection between psoriasis and  cardiovascular damage, as well as the need for further in-depth studies on the subject,  as well as methods for screening, prevention, and treatment of cardiovascular risk  factors in psoriasis patients.